Toksisitas Subletal Limbah Cair Batik Hasil Biosorpsi terhadap Hematokrit Ikan Mas (Cyprinus carpio) - Nur Hidayati; Sri Lestari; Eko Setio Wibowo (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2019)
Research on the hematocrit value of fish exposed to batik wastewater resulted from the biosorption process needed because the blood is one indicator of contaminants present that entering the fish body. This research aims to determine the effects of batik wastewater resulted from biosorption process exposure on Carp (Cyprinus carpio) hematocrit value. The treatments are batik wastewater resulted from biosorption process with different concentrations, i.e 0; 1,32; 2.64 and3, 96 % v.v-1. The carp maintained for 7 days and the blood was taken in the 8 days. Measured variables were hematocrit value. The result shows that the highest of the hematocrit in 0%v/v-1 concentration was 31.67±1.49 % while the lowest in 3,96 % v.v-1 concentration was 26.00±1.15 %. The conclusion, that batik wastewater resulted from the biosorption process induced a significant increase in the hematocrit value.